Implementation of Traditional Game-Based Inquiry Learning Model to Improve Students' Speaking and Reading Skills Class 1 - Herawati Djabbar; Rahmawati Rahmawati; Nasaruddin Nasaruddin (ALENA : Journal of Elementary Education, 2026)
Early literacy is a crucial foundation for the development of elementary school students' language skills, especially in the lower grades. However, in practice, students still experience difficulties in reading and speaking skills due to a lack of varied learning and the failure to fully engage students actively. Therefore, learning innovations are needed that are engaging, contextual, and tailored to the characteristics of early childhood students. This research aims to improve skills reading and speaking students through application of inquiry- based learning models game traditional hide- and-seek Literacy in first grade students of SD Negeri 60 Moncongloe Lappara. This research is a Classroom Action Research (CAR) which was carried out in two cycles based on the Kemmis and McTaggart model, which includes the planning and implementation stages action, observation, and reflection. The research subjects consisted of 30 first -grade students of SD Negeri 60 Moncongloe Lappara. Data collection techniques using observation, tests reading and speaking simple, as well as documentation of learning activities. Data analysis was carried out descriptive quantitative and qualitative to see the improvement in student learning outcomes in each cycle. The results of the study showed an increase in ability students' reading and speaking at each stage of the action. The average pre -test score action was 67.80, increasing to 72.47 in cycle I, and 78.10 in cycle II. The percentage increased learning completion from 26.67% to 66.67% and reached 90% in cycle II. Thus, the application of the inquiry- based learning model game traditional proven effective in improving skills early literacy of first grade students at SD Negeri 60 Moncongloe Lappara.